Constitutional Morality in India: A Critical Study of Judicial Vision - Anis Ahmad,; Nikki Kumar, (AG Volumes, 2026)
India is among the few in the world as a democratic, sovereign State having a Constitutional vision for the governance of country and its peoples. The very principle was introduced by the Dr. B.R. Ambedkar in the Constitutional Assembly. The concept of Constitutional morality which is dynamic and an evolving within the realm of Constitutional law and jurisprudent. It asserts that the Constitution of India should not only be a legal document but a moral one. It emphasizes the application of constitutional provisions in a manner that upholds the foundational values of justice, equality, liberty, and dignity as given in preambular ideals of the Constitution treated as basic structure by the process of judicial review.  The decisions of the courts since the Keshavananda Bharti Case has exemplified the pivotal role of the judiciary in interpreting and safeguarding principle of constitutional morality. This chapter aims to explore the judicial perspective on constitutional morality, examining its critical legal analysis through landmark cases and legal developments.